Mitochondrial genome insights into the phylogenetics and biogeographic evolution of snow trout (Cyprinidae, Schizothorax) in the Tien Shan Mountains - Akbarjon Rozimov; Yufan Wang; Min Wang; Ming Zou; Jobir Sobirov; Erkin Karimov; Bakhtiyor Kholmatov; Jörg Freyhof; Sirojiddin Namozov; Chongnv Wang; Xinxin Li; Baocheng Guo (Zoosystematics and Evolution)
Snow trout (Schizothorax), endemic to the high-altitude freshwater systems of the Tibetan Plateau and the Tien Shan Mountains region, are key components of these ecosystems. This fish lineage may serve as an appropriate model to understand the evolution of biodiversity in the Tien Shan Mountain water ecosystems. However, research has been hindered by poorly understood phylogenetic relationships, unresolved taxonomic classifications, and ambiguous biogeographical histories, particularly in the underexplored western regions of the Tien Shan Mountains. Here, we analyzed three mitochondrial genomes assembled using the next-generation sequencing data of three snow trout species, S. eurystomus, S. fedtschenkoi, and Schizothorax sp., from the western Tien Shan Mountains. These genomes range from 16,584 to 16,592 bp in length and include 13 protein-coding genes (PCGs), 2 rRNAs, 22 tRNAs, and a control region. Our phylogenetic analyses suggest six snow trout from the Tien Shan Mountains region were divided into two distinct clades: clade I comprises S. fedtschenkoi, and Schizothorax sp., and clade II includes S. eurystomus, S. biddulphi, S. pseudoaksaiensis, and S. argentatus. We classified Schizothorax sp. as a valid independent species based on comprehensive phylogenetic trees and DNA barcode genetic distance. The dramatic uplift of the Tien Shan Mountains during the Late Miocene to the Pliocene, followed by periods of isolation on its eastern and western flanks, has driven extensive speciation, contributing to the rich diversity observed today. Notably, S. eurystomus spread westward along the Pamir-Tien Shan corridor, shaping the region’s current biogeographical distribution of snow trout species. Our findings not only clarify the evolutionary histories of snow trout in the Tien Shan Mountains but also advance our understanding of the mechanisms shaping the rich biodiversity.